Long‐Term Selection in Hybrid Sorghum Breeding Programs. Issue 1 (1st January 2019) - Pfeiffer, Brian K.; Pietsch, Dennis; Schnell, Ronnie W.; Rooney, William L.
Abstract : Estimating genetic gains in sorghum [ Sorghum bicolor (L.) Moench] is necessary to assess whether the current rates of improvement will meet future production demands. The current study was conducted to determine the rate of genetic gain in yield and associated traits over the commercial hybrid era using sorghum germplasm from the Texas A&M sorghum breeding program and a US sorghum seed company. From the Texas A&M AgriLife program, 60 hybrids that represented a 50‐yr span of hybrid breeding were grown and evaluated in five environments across Texas in 2016. In a separate set of trials, 14 commercial hybrids representing a similar timespan were evaluated in three Texas environments in 2016. In both programs, grain sorghum yields increased 0.008 t ha −1 annually over their respective timespans. Traits that increased over time included yield potential per plant, heterosis, test weight, panicle size, and grain number per panicle, whereas leaf angle, days to maturity, plant height, and yield stability demonstrated little to no change. Overall, ∼60% of total yield gains in US sorghum production are attributed to genetic improvement through sorghum breeding. Compared with other major US field crops, the rate of genetic gain in sorghum has been slower, presumably due to a combination of factors, which include continually shifting production environments, changing priorities in traits, reduced research investments (compared with other crops), and less‐than‐optimized heterotic groups.